1998
DOI: 10.1021/jp981412l
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Radicals in Aryl-Substituted Polysilanes with Linear and Planar Silicon Skeleton Structures

Abstract: This paper discusses the stability of radicals produced under γ-irradiation for phenyl-substituted polysilanes with different backbone structures. Poly(methylphenylsilane) and structural defect-containing phenyl-substituted polysilanes were irradiated by 60Co γ-rays in the solid state. Temperature dependence of the EPR signal intensity from the radicals induced by radiolysis was measured. The radicals appeared to be more stable as the induced defect density in the backbone structure was increased, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…For example, G(s) and 9 G(x) values of poly(di-n-butylsilane) which has the similar structure to PMPrS are 0.42 and 0.023, respectively. Although aryl-substituted polysilanes have relatively higher G(x) values than alkyl-substituted polysilanes due to the protecting effect by aryl groups, still the chains of aryl-substituted polysilanes are also degraded by -rays (Seki et al, 1998). We also confirmed that PMPrS is degraded by -irradiation (Tanaka et al, 2011).…”
Section: Synthesis Of Pmprs-g-paasupporting
confidence: 72%
“…For example, G(s) and 9 G(x) values of poly(di-n-butylsilane) which has the similar structure to PMPrS are 0.42 and 0.023, respectively. Although aryl-substituted polysilanes have relatively higher G(x) values than alkyl-substituted polysilanes due to the protecting effect by aryl groups, still the chains of aryl-substituted polysilanes are also degraded by -rays (Seki et al, 1998). We also confirmed that PMPrS is degraded by -irradiation (Tanaka et al, 2011).…”
Section: Synthesis Of Pmprs-g-paasupporting
confidence: 72%
“…Despite positive charge being the dominant charge carriers in the transport process, there have been few dynamics or quantitative analyses on the electronic state of positive charges on the Si or Ge chain other than by transient spectroscopy 12,13 or electron spin resonance. 14,15 Localization of the charge carriers was revealed to be suppressed in the -conjugated polymers bearing bulky pendant groups, suggesting not only that the localization in typical dialkyl substituted polymers arises from the flexibility of Si(Ge) catenation, but also that delocalization occurs in -conjugated polymers with stiff or rod-like skeletons. However, the quantitative correlation between the molecular stiffness and the degree of positive charge delocalization had not been elucidated to date.…”
Section: -4mentioning
confidence: 99%
“…However, the GðxÞ derived from this fit are almost identical to those in Table III, depending on the molecular weight, because the values are estimated in the low-dose region where eq 18 is sufficiently linearity. The effects of the polymer structure 15 and the cross- linking precursor species 86 have been considered in previous studies, where it was revealed that there was less of a dependence of GðxÞ on the molecular weight in the case of -rays or electron beam irradiation. The cross-linking points in polymer materials are distributed non-homogeneously on an ion track along an ion trajectory.…”
Section: Intrinsic Mobility Of Charge Carriers Along -Conjugated Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…the evaluation of the thermal oxidative stabilization obtained from grafting HALS groups, NH 2 -R-NH-(4-aza-3-dimethyl-5-dimethyl-cyclohexane), where R D CH 2 2or6 , onto anhydride functionalized poly(organophosphazene) molecules (52), 2. both the characterization and stability of -irradiated polysilane radicals (53), and 3. the autooxidation of poly(hydrosilane)s after uptake using fusinite as a paramagnetic probe (54).…”
Section: Electron Paramagnetic Resonance Spectroscopymentioning
confidence: 99%